Prioritization of types of investments: Operational tools for MCC agricultural investments - Laborde Debucquet, David; Parent, Marie; Piñeiro, Valeria (International Food Policy Research Institute, 2021)
This report answers the question: “What guidelines can be used to identify the types of agricultural investments that have the highest economic return, where “agriculture” is broadly defined to include primary production, handling, storage, transportation, distribution, processing, and retailing?” Using the literature and MCC’s ERR analyses, we explain how agricultural investments fit in a wider development context, identify information useful to MCC’s decision making that is not provided by the ERR analyses, and suggest IFPRI tools for exploratory and ex-ante evaluative analysis that MCC can use in their decision-making process.